The History of Decompressive Craniectomy in Traumatic Brain Injury - Rossini, Zefferino; Nicolosi, Federico; Kolias, Angelos G.; Hutchinson, Peter J.; De Sanctis, Paolo; Servadei, Franco (Frontiers in Neurology, 2019)
Decompressive craniectomy consists of removal of piece of bone of the skull to reduce intracranial pressure. It is an age-old procedure, taking ancient roots from the Egyptians and Romans, passing through the experience of Berengario da Carpi, until Theodore Kocher, who was the first to systematically describe this procedure in traumatic brain injury. In the last century, many neurosurgeons have reported their experience, using different techniques of decompressive craniectomy following head trauma, with conflicting results. It is thanks to the successes and failures reported by these authors that we are now able to better understand the pathophysiology of brain swelling in head trauma and the role of decompressive craniectomy in mitigating intracranial hypertension and its impact on clinical outcome. Following a historical description, we will describe the steps that led to the conception of the recent randomized clinical trials, which have taught us that decompressive craniectomy is still a last-tier measure, and decisions to recommend it should been made not only according to clinical indications but also after consideration of patients’ preferences and quality of life expectations.